Síntese de pirido/benzo[b][1,4]selenazinas e 1,3-selenazóis 2-acil-substituídos a partir de disselenetos de (bis)orto-amino (hetero)arila - Santos, Felipe Boz (2024)
In this thesis, a synthesis methodology was developed to obtain two groups of isomers from the class of pyrido/benzo[b][1,4]selenazines through the cyclocondensation reaction between (bis)ortho-amino (hetero)aryl diselenides and β-diketones, via selective I2 catalysis. The work began with a series of experiments focused on determining the best reaction conditions to obtain the compound Z-1-(1H-pyrido[2,3-b][1,4]selenazin-2(3H)-ylidene)propan-2-one. The developed methodology enabled the obtaining of a series of 22 examples of pyrido/benzo[b][1,4]selenazines, via iodine catalysis, with yields ranging from 53% to 86%. Additionally, a second series with five examples of pyrido/benzo[b][1,4]selenazine isomers was obtained in the absence of a catalyst, with yields ranging from 44% to 71%. To evaluate the reactivity of the obtained compounds, a model example of pyrido/benzo[b][1,4]selenazine was chosen to be employed in cyclocondensation and oxidation reactions. This study resulted in the compound 2-(((5-methyl-1H-pyrazol-3-yl)methyl)selanyl)pyridin-3-amine with a yield of 72%. The oxidation reaction was based on the use of m-CPBA as an oxidizing agent, resulting in the product (Z)-2-(2-oxopropylidene)-2,3-dihydro-1H-pyrido[2,3-b][1,4]selenazin-3-yl 3-chloro-benzoate, with a yield of 70%. Finally, tests were conducted using ultrasound irradiation as an alternative energy source. This approach resulted in a significant reduction in reaction time, from 10 hours to 30 minutes, compared to the conventional method of heating with an oil bath. The thesis also addresses the synthesis of 1,3-pyrido/benzoselenazoles 2-acyl-substituted, obtained through the cyclocondensation reaction between (bis)ortho-amino (hetero)aryl diselenides and substituted methyl-ketones using Na2CO3, DMA as solvent, and temperature of 90 °C. The developed methodology allowed the obtaining of eight examples of 1,3-pyrido/benzoselenazoles 2-acyl-substituted with yields ranging from 48% to 72%. All the compounds presented in this thesis were characterized by nuclear magnetic resonance, 1H NMR, 13C NMR, and melting point. Additionally, selected examples, considered strategic, were subjected to x-ray diffraction analysis.